2020
DOI: 10.2147/cmar.s249790
|View full text |Cite
|
Sign up to set email alerts
|

<p>Spread Through Air Spaces (STAS) in Lung Cancer: A Multiple-Perspective and Update Review</p>

Abstract: Background: Spread through air spaces (STAS) is a spreading phenomenon of lung cancers, which is defined as tumor cells within air spaces in the lung parenchyma beyond the edge of the main tumor. To date, several articles have reviewed the studies concerning the significance of STAS; however, most articles focused on the prognosis without summarizing the significance of STAS on other aspects. In this review, we comprehensively summarized the current literature related to STAS, so as to explore the clinical sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 54 publications
0
22
1
2
Order By: Relevance
“…Fourth, our prediction model was solely based on imaging features because our main hypothesis was that the imaging features could reflect the information of the existence of STAS. However, clinical factors such as age, gender, and serum carcinoembryonic antigen are also reported to be predictors of STAS, and the addition of these factors may lead to a more predictive model 27 . Lastly, there is room to further reduce data sampling bias by applying sophisticated methods to building a prediction model, such as nested cross validation; however, we needed to leave a test cohort aside in advance for the following survival outcome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, our prediction model was solely based on imaging features because our main hypothesis was that the imaging features could reflect the information of the existence of STAS. However, clinical factors such as age, gender, and serum carcinoembryonic antigen are also reported to be predictors of STAS, and the addition of these factors may lead to a more predictive model 27 . Lastly, there is room to further reduce data sampling bias by applying sophisticated methods to building a prediction model, such as nested cross validation; however, we needed to leave a test cohort aside in advance for the following survival outcome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, STAS is not a pattern of invasion but just an artefact associated with lung resection and specimen preparation (tumour cells displaced by the knife along the plane of sectioning) [ 39 , 40 ]. Furthermore, from a biological perspective, the cells can't live on air [ 41 , 42 ]. However, STAS has been observed without cutting through the main tumour [ 43 ], and, with the help of three-dimensional reconstruction, it has been found that detached tumour islands, after migration through air spaces, reattach in close apposition to alveolar vessels, which is a potential mechanism for cell survival [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor spread through air spaces (STAS) was reported as a novel poor prognostic factor in the latest World Health Organization (WHO) classi cation (2). In recent studies, STAS in patients with lung cancer was shown to be associated with high recurrence rates and poor survival after surgical resection (3,4). We consider that the size of DBRM may affects STAS, which in turn affects the prognosis.…”
Section: Introductionmentioning
confidence: 98%